77.7k views
3 votes
6x+5y=39
3x+5y=27
Solveing systems by elimination

User Gpvos
by
5.0k points

2 Answers

6 votes
6x + 5y = 39 ......(i)

3x + 5y = 27.....(ii)

Because of the 5y in both equations (i) and (ii), we subtract, so as to eliminate y

6x + 5y = 39 ......(i)
-
3x + 5y = 27.....(ii)
______________
3x + 0 = 12


3x = 12
x = 12/3 = 4, x = 4.

Substituting into 3x + 5y =27, x = 4

3*4 + 5y = 27

12 + 5y = 27

5y = 27 - 12

5y = 15

y = 15/5

y = 3

So the solutions are x = 4, y = 3.

Hope this helped.
User GerardBeckerleg
by
6.0k points
1 vote
X=4 and Y=3 If you need to the work shown I can put a picture
User Nathan Bush
by
7.0k points